In a Pure Muslim Land : Shi'ism between Pakistan and the Middle East - Fuchs, Simon Wolfgang, 1982- (Islamic civilization & Muslim networks., 2019)
Centering Pakistan in a story of transnational Islam stretching from South Asia to the Middle East, Simon Wolfgang Fuchs offers the first in-depth ethnographic history of the intellectual production of Shi'is and their religious competitors in this "Land of the Pure." The notion of Pakistan as the pinnacle of modern global Muslim aspiration forms a crucial component of this story. It has empowered Shi'is, who form about twenty percent of the country's population, to advance alternative conceptions of their religious hierarchy while claiming the support of towering grand ayatollahs in Iran and Iraq. Fuchs shows how popular Pakistani preachers and scholars have boldly tapped into the esoteric potential of Shi'ism, occupying a creative and at times disruptive role as brokers, translators, and self-confident pioneers of contemporary Islamic thought. They have indigenized the Iranian Revolution and formulated their own ideas for fulfilling the original promise of Pakistan. Challenging typical views of Pakistan as a mere Shi'i backwater, Fuchs argues that its complex religious landscape represents how a local, South Asian Islam may open up space for new intellectual contributions to global Islam. Yet religious ideology has also turned Pakistan into a deadly battlefield: sectarian groups since the 1980s have been bent on excluding Shi'is as harmful to their own vision of an exemplary Islamic state.